1997
DOI: 10.1038/ki.1997.238
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibroblast growth factors and their receptors in rat glomeruli

Abstract: Fibroblast growth factors (FGFs) regulate cell proliferation and differentiation, and are also important regulators of extracellular matrix. They are among the most potent angiogenic factors known. Evidence suggests the FGFs play a role in glomerular development and pathology. The aim of the present study was to determine whether FGF-1 (acidic FGF) and FGF-2 (basic FGF) and their receptors (FGFRs) were expressed in normal adult rat glomeruli, using reverse transcriptase-polymerase chain reaction (RT-PCR) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…Fgfr1 was present in kidney mesenchymal cells regardless of their genetic status, as reported earlier (Dudley et al, 1999;Ford et al, 1997;Walshe and Mason, 2000), but its expression was lost in the more mature nephrons in the presence of human SPRY2, unlike the situation in the controls (Fig. 3, compare E with E′,E′′), suggesting that human SPRY2 expression has an influence on the maturation of the nephron, apparently owing to deregulated ureteric bud inductive signalling.…”
Section: Expression Of the Genes Encoding Fgf And Egf Proteins Theirmentioning
confidence: 49%
“…Fgfr1 was present in kidney mesenchymal cells regardless of their genetic status, as reported earlier (Dudley et al, 1999;Ford et al, 1997;Walshe and Mason, 2000), but its expression was lost in the more mature nephrons in the presence of human SPRY2, unlike the situation in the controls (Fig. 3, compare E with E′,E′′), suggesting that human SPRY2 expression has an influence on the maturation of the nephron, apparently owing to deregulated ureteric bud inductive signalling.…”
Section: Expression Of the Genes Encoding Fgf And Egf Proteins Theirmentioning
confidence: 49%
“…Expression of FGF2 and FGFR1 mRNA in normal rat kidneys has been detected using Northern blotting [7,30]. Expression of FGF and FGFR isoform mRNA in whole cortex and isolated glomeruli has also been demonstrated using the RT-PCR method [9]. We were unable to demonstrate mRNA for any of the FGFRs in normal rat glomeruli using an in situ hybridization method.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, FGF2 has been found in mesangial areas, the glomerular basement membrane, glomerular epithelial cells, the basement membrane of Bowman's capsule, small arterial walls, and tubules of the normal kidney using the immunohistochemical method [7,26]. In an immunohistochemical study using frozen sections, expression of FGFRs 1-4 in normal glomeruli was observed [9]. It has recently been reported that the immunolocalization patterns for FGF2 differ according to the fixative or preparation technique used, and depending on the antibody specificity [3,12].…”
Section: Discussionmentioning
confidence: 92%
“…36 Furthermore, rat glomeruli express various forms of FGFs and FGFRs. 37 In other types of glomerulonephritis, glomeruli may become infiltrated with inflammatory cells, eg, macrophages or platelets, which are sources of epithelial growth factors, including transforming growth factor-␣, EGF, and bFGF. 38,39 Production of HGF in intrinsic glomerular cells (eg, mesangial cells) might increase.…”
Section: 13mentioning
confidence: 99%